تحديات شرط الواقف في استخدام الوقف لمواجهة الجائحة العالمية كوفيد-19: CHALLENGES OF CONDITION OF WAQIF IN USING WAQF AS A RELIEF TOOL TO FIGHT AGAINST THE COVID-19 PANDEMIC - zakariyah, habeebullah; Bature, Habeebullah Hassan (Malaysian Journal of Syariah and Law, 2021)
Abstract in English:Waqf (Islamic Endowment) has played a vital role in solving the social problems throughout the history.  This paper aims at discussing the role of waqf in tackling the current global pandemic i.e., COVID -19.  The paper discusses the possibility of using waqf as a mechanism for mitigating the negative effect of the COVID-19 pandemic.  Considering the strong connection between waqf and the stipulated conditions by the waqif (donor), the paper analyses the views of the past and contemporary jurists on the extent of the permissibility of overriding the conditions of the donor (shart al-waqif) by the waqf management.  This paper adopts qualitative methodology, and the textual analysis is being used by reviewing the literature and previous studies related to the issue.  The paper reaches some conclusions, the most important of which are: the confirmation of the vital role of waqf in alleviating the severity of COVID-19 pandemic.  Likewise, waqf management is permitted to breach the conditions of the waqif if the need is warranted and the objective of waqf is being considered.  To avoid the challenges of shart al-waqif (conditions of the waqif), the paper proposes the establishment of waqf, which will be looking after the interest and affairs of the victims of crises “waqf for azamat”.  Besides, the paper recommends to the researchers and waqf managements reviewing of the structure of the Crises-Waqf. Abstract in Arabic:مشروع الوقف الإسلامي من الوسائل المهمة في تحقيق التنمية الاجتماعية وله دور عظيم في المشكلات التي تواجه المجتمع.  الهدف من هذه الدراسة الوقوف على الأدوار يمكن أن يلعبه الوقف الإسلامي في مواجهة فيروس كورونا ما يسمى ب" كوفيد-19 " . تمت مناقشة مدى جواز توظيف الوقف الإسلامي كوسيلة لتقليل الآثار السلبية التي نجمت من هذا الفيروس. ولا شك أن للوقف الإسلامي علاقة وطيدة بشرط الواقفين لذلك حاولت الدراسة الوقوف على آراء الفقهاء قديما وحديثا، ومن ثم تحليلها لمعرفة مدى إمكانية خروج المؤسسات الوقفية عن شرط الواقفين. تم توظيف منهج البحث النوعي التحليلي من خلال مراجعة الأدبيات والدراسات السابقة المتعلقة بهذه المسألة. توصلت هذه الدراسة إلى جملة من النتائج، من أهمها: أن للوقف الإسلامي دوراً كبيرا في التنمية الاجتماعية ويمكن استخدامه في مواجهة فيروس كورونا- كوفيد-19، كما أظهرت نتائج البحث أنه يجوز لناظر الوقف أو المؤسسات الوقفية الخروج من شرط الواقفين إذا دعت الحاجة إلى ذلك، مع مراعاة مصلحة الوقف. وخروجاً من مشكلة شرط الواقف، تقترح هذه الدراسة للمؤسسات الوقفية إنشاء وقف إسلامي يهتم برعاية شؤون المتضررين من الأزمات "وقف الأزمات"، كما توصي الورقة المؤسّسات الوقفية والباحثين بالعمل في إنشاء "وقف الأزمات".